Implementation Of Online Learning Policy In Indonesia - Kus Indarto; Susi Ratnawati; Nurul Umi Ati; Adheline Putriyanti (Syntax Literate, 2022)
Online learning methods or distance learning are an unavoidable choice, during the Covid-19 pandemic. The teaching-learning process, which is usually carried out in the classroom, is shifted to homes using existing technology, using computers, laptops, or cellphones. This is done to prevent the spread of the Covid-19 virus so that educators and students are both safe. The purpose of this study is to describe and analyze the implementation of online learning policies in Indonesia, along with the inhibiting and supporting factors. This study uses a qualitative approach with a descriptive method. Data is collected by looking for journals and other sources on the internet or a literature study. Furthermore, the data obtained were analyzed using interactive model data analysis according to Miles, Huberman, and Saldana (2014). The results in this study are 1) communication has not fully worked well; 2) resources, it is still necessary to increase the capacity of human resources, facilities and infrastructure are still lacking; 3) disposition, there are still many teachers who are not committed to implementing online learning, some lecturers also do not understand the essence of online learning; 4) bureaucratic structure, most educational institutions already have standard operating procedures. The most dominant inhibiting factor is the poor internet network connection, while the supporting factors for some places have good human resources, as well as the facilities and infrastructure.